Influence of carbohydrate on the microparticulation process of whey proteins: structural modifications and indicators of the Maillard Reaction - Igor L. de Paula; Natalia C. Mesa; Alan F. Wolfschoon-Pombo; Uwe Schwarzenbolz; Thomas Henle; Ítalo T. Perrone; Luiz Fernando C. de Oliveira; Rodrigo Stephani (International Dairy Journal, 2026)

Correction: Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanne Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)

Progress status of the NUSES Space Mission - M. Abdullahi; R. Aloisio; S. Ashurov; U. Atalay; F.C.T. Barbato; R. Battiston; M.E. Bertaina; E. Bissaldi; D. Boncioli; L. Burmistrov; I. Cagnoli; E. Casilli; et al. (Advances in Space Research, 2026)

Hereditary gynecological cancer management in women with Lynch syndrome: a survey across Europe - Kevin J. J. Kwinten; Joanne A. de Hullu; Helen Bolton; Monique M. A. Brood-van Zanten; Valentina Chiappa; Stefan Cosyns; Sergi Fernandez-Gonzalez; Angelique Flöter Rådestad; Sophie Frank; Rieke Gellner; Susanna Housmans; Nina Kovacevic; et al. (Familial Cancer, 2026)
We aim to compare clinical practices in the gynecological management of women with Lynch syndrome across Europe and assess the need for multidisciplinary gynecological care for this high-risk population. European gynecologists involved in the clinical care of women with Lynch syndrome were invited to complete a cross-sectional survey regarding their clinical practices and organization of care. All participating gynecologists were based in hospitals that are members of the European Reference Network on Genetic Tumour Risk Syndromes (ERN GENTURIS). A total of 33 gynecologists (57%) from 25 unique hospitals across 12 countries participated in the survey. National guidelines on the gynecological management of women with Lynch syndrome were absent in a significant number of European countries. Local multidisciplinary team meetings were available in 61% of hospitals. Considerable heterogeneity was reported in the organization of care, as well as in surveillance, prevention, and treatment strategies. Standardized European guidelines for the gynecological care of women with Lynch syndrome are warranted to promote uniformity. Gynecologists specialized in hereditary cancer should take the lead in developing and implementing these guidelines. Hospitals managing women with Lynch syndrome should have the resources to organize multidisciplinary team meetings, which are crucial for the effective implementation of these guidelines and the improvement of personalized care.

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

Early effects of anti-TNFα antibodies in horses with osteoarthritis - G. Perrone; C. Giampaoli; A. Lorenzo Smirnoff; A. Ochoa; R. Pareja; E. De Simone (Journal of Equine Veterinary Science, 2025)

A multidisciplinary approach to estimating wolf population size for long‐term conservation - Francesca Marucco; Maria V. Boiani; Pierre Dupont; Cyril Milleret; Elisa Avanzinelli; Kristine Pilgrim; Michael K. Schwartz; Achaz von Hardenberg; Domenica Serena Perrone; Olivier P. Friard; Arianna Menzano; Francesco Bisi; et al. (Conservation Biology, 2023)
The wolf ( Canis lupus ) is among the most controversial of wildlife species. Abundance estimates are required to inform public debate and policy decisions, but obtaining them at biologically relevant scales is challenging. We developed a system for comprehensive population estimation across the Italian alpine region (100,000 km 2 ), involving 1513 trained operators representing 160 institutions. This extensive network allowed for coordinated genetic sample collection and landscape‐level spatial capture–recapture analyses that transcended administrative boundaries to produce the first estimates of key parameters for wolf population status assessment. Wolf abundance was estimated at 952 individuals (95% credible interval 816–1120) and 135 reproductive units (i.e., packs) (95% credible interval 112–165). We also estimated that mature individuals accounted for 33–45% of the entire population. The monitoring effort was spatially estimated thereby overcoming an important limitation of citizen science data. This is an important approach for promoting wolf–human coexistence based on wolf abundance monitoring and an endorsement of large‐scale harmonized conservation practices.

Revised Accelerated Moment Release Under Test: Fourteen Worldwide Real Case Studies in 2014–2018 and Simulations - Gianfranco Cianchini; Angelo De Santis; Rita Di Giovambattista; C. Abbattista; L. Amoruso; S. A. Campuzano; M. Carbone; C. Cesaroni; Anna De Santis; D. Marchetti; L. Perrone; A. Piscini; et al. (Pure and Applied Geophysics, 2020)

The microRNA-29a Modulates Serotonin 5-HT7 Receptor Expression and Its Effects on Hippocampal Neuronal Morphology - Floriana Volpicelli; L. Speranza; S. Pulcrano; R. De Gregorio; M. Crispino; C. De Sanctis; M. Leopoldo; E. Lacivita; U. di Porzio; G. C. Bellenchi; C. Perrone-Capano (Molecular Neurobiology, 2019)

Seismic performance of non-structural elements during the 2016 Central Italy earthquake - D. Perrone; P. M. Calvi; R. Nascimbene; E. C. Fischer; G. Magliulo (Bulletin of Earthquake Engineering, 2019)

Multimodal Neuroimaging in Schizophrenia: Description and Dissemination - C. J. Aine; H. J. Bockholt; J. R. Bustillo; J. M. Cañive; A. Caprihan; C. Gasparovic; F. M. Hanlon; J. M. Houck; R. E. Jung; J. Lauriello; J. Liu; A. R. Mayer; et al. (Neuroinformatics, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Contribution of EARLINET/ACTRIS to the summer 2013 Special Observing Period of the ChArMEx project: monitoring of a Saharan dust event over the western and central Mediterranean - M. Sicard; R. Barragan; C. Muñoz-Porcar; A. Comerón; M. Mallet; F. Dulac; J. Pelon; L. Alados Arboledas; A. Amodeo; A. Boselli; J. A. Bravo-Aranda; G. D’amico; et al. (International Journal of Remote Sensing, 2016)

Purple Glove Syndrome after Phenytoin or Fosphenytoin Administration: Review of Reported Cases and Recommendations for Prevention - Lyudmila A. Garbovsky; Byron C. Drumheller; Jeanmarie Perrone (Journal of Medical Toxicology, 2015)

Prevalence of respiratory colonisations and related antibiotic resistances among paediatric tracheostomised patients of a long-term rehabilitation centre in Italy - M. Pozzi; P. Pellegrino; S. Galbiati; M. Granziera; F. Locatelli; C. Carnovale; V. Perrone; S. Antoniazzi; C. Perrotta; S. Strazzer; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Epidemiological analysis on two decades of hospitalisations for meningitis in the United States - P. Pellegrino; C. Carnovale; V. Perrone; D. Salvati; M. Gentili; T. Brusadelli; S. Antoniazzi; M. Pozzi; S. Radice; E. Clementi (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Cystic fibrosis Δf508 mutation screening in Brazilian women with altered fertility - G. V. F. Brunoro; E. V. Wolfgramm; I. D. Louro; I. I. Degasperi; V. C. W. Busatto; A. M. S. Perrone; M. C. P. Batitucci (Molecular Biology Reports, 2011)

Developmental stages of attachment of in vitro protoplasts in two Mediterranean Valonia species (Siphonocladales, Chlorophyta) - A. Bottalico; G. P. Felicini; C. I. Delle Foglie; C. Perrone (Plant Biosystems, 2008)

A Biomonitoring Study Assessing the Residual Biological Effects of Pollution Caused by the HAVEN Wreck on Marine Organisms in the Ligurian Sea (Italy) - A. Viarengo; F. Dondero; D. M. Pampanin; R. Fabbri; E. Poggi; M. Malizia; C. Bolognesi; E. Perrone; E. Gollo; G. P. Cossa (Archives of Environmental Contamination and Toxicology, 2007)

Neonatal pain analyzer: development and validation - R. Sisto; C. V. Bellieni; S. Perrone; G. Buonocore (Medical & Biological Engineering & Computing, 2006)

Developmental morphology of Acanthophora nayadiformis (Rhodophyta, Ceramiales): Sympodial growth and propagule germination - C. Perrone; E. Cecere; C. I. Delle Foglie (Plant Biosystems, 2005)

Persistent Organochlorine Pollutants in Liver of Birds of Different Trophic Levels from Coastal Areas of Campania, Italy - B. Naso; D. Perrone; M. C. Ferrante; A. Zaccaroni; A. Lucisano (Archives of Environmental Contamination and Toxicology, 2003)

Molecular and Biochemical Characterization of Two Atypical Toxigenic Populations of Fusarium Camptoceras - G. Mule’; C. Altomare; A. Moretti; G. Perrone; A. Logrieco (Cereal Research Communications, 1997)

Fusapyrone and Deoxyfusapyrone from Fusarium semitectumi Production and Biological Activities - C. Altomare; G. Perrone; M. C. Zonno; L. Polonelli; A. Evidente (Cereal Research Communications, 1997)